Physiologically based pharmacokinetic modeling of cefotaxime to inform pediatric dosing in renal impairment - Najia Rahim; Muhammad Sarfraz; Muhammad Wahajuddin (European Journal of Clinical Pharmacology, 2026)
Background Cefotaxime (CFT) is a broad spectrum, third-generation cephalosporin antibiotic prescribed for the treatment of severe infections, yet dosing guidelines for pediatric with renal impairment is scarce. The current study aimed to develop a physiological based pharmacokinetic (PBPK) model to characterize CFT disposition and model-based recommend dose adjustments in pediatrics with renal impairment. Methods Initially, the PBPK model of CFT was developed in adults with normal renal function before being scaled to pediatrics, considering age-related physiological changes using GastroPlus® software. Renal impairment was modelled through optimization of tubular secretion and glomerular filtration parameters based on observed data for both adults and pediatric populations. Results The model reasonably reproduced the observed pharmacokinetic profiles and showed acceptable agreement with the data (fold error ranges 0.84–1.37) or with renal impairment (fold error ranges 0.87–1.12). When compared to children with normal renal function, the predicted AUC0−∞ in children with renal impairment increased to 1.22- and 1.89-fold for moderate and severe renal impairment, respectively. Model-informed dose recommendations were 60% and 48% of the standard pediatric dose for moderate and severe renal impairment, respectively. Conclusion This PBPK framework supports rational, model-informed dosing of CFT in pediatric patients with varying renal impairment and supports dose recommendation development for high-risk populations.

Innovative Nanocarriers of Sorafenib in the Optimisation of Therapeutic Outcome: Challenges and Applications in Breast Cancer - Nishtha Chaurawal; Amalia Ruiz Estrada; Klaus Pors; Kaisar Raza; Muhammad Wahajuddin (AAPS PharmSciTech, 2026)

Docetaxel-tethered di-Carboxylic Acid Derivatised Fullerenes: A Promising Drug Delivery Approach for Breast Cancer - Charu Misra; Jasleen Kaur; Manish Kumar; Lokesh Kaushik; Deepak Chitkara; Simran Preet; Muhammad Wahajuddin; Kaisar Raza (AAPS PharmSciTech, 2024)

Dietary Isoflavones as Modulators of Drug Metabolizing Enzymes and Transporters: Effect on Prescription Medicines - Isha Taneja; Kanumuri Siva Rama Raju; Muhammad Wahajuddin (Critical Reviews in Food Science and Nutrition, 2016)